2013
DOI: 10.1371/journal.pone.0075023
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Modulation of Psychophysical, Respiratory and Autonomic Responses to Cold Pressor Test

Abstract: In healthy subjects with high hypnotisability (highs) under hypnosis, subjectively effective suggestions for analgesia abolish the increases in blood pressure associated with cold pressor test (cpt) by reducing the peripheral vascular resistance. The aim of the present study was to investigate the effects of the suggestions of analgesia on the responses to cpt in healthy highs (n = 22) and in low hypnotisable participants (lows, n = 22) out of hypnosis. Cpt was administered without (CPT) and with suggestions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…For example, researchers are beginning to examine additional biological factors associated with hypnosis such as changes in peripheral hormone levels (Bryant, Hung, Guastella, & Mitchell, 2012; Varga & Kekecs, 2014), heart rate and heart rate variability (Santarcangelo et al, 2012; Santarcangelo, Varanini et al, 2013; Sebastiani, Simoni, Gemignani, Ghelarducci, & Santarcangelo, 2003; Yuksel, Ozcan, & Dane, 2013), respiratory rate (Sebastiani et al, 2003), and blood pressure (Santarcangelo, Paoletti et al, 2013). Doubtless some of these factors as well as other biological, psychological, and social factors not examined here will be identified as being associated with, and may ultimately be shown to influence, hypnotic responding.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers are beginning to examine additional biological factors associated with hypnosis such as changes in peripheral hormone levels (Bryant, Hung, Guastella, & Mitchell, 2012; Varga & Kekecs, 2014), heart rate and heart rate variability (Santarcangelo et al, 2012; Santarcangelo, Varanini et al, 2013; Sebastiani, Simoni, Gemignani, Ghelarducci, & Santarcangelo, 2003; Yuksel, Ozcan, & Dane, 2013), respiratory rate (Sebastiani et al, 2003), and blood pressure (Santarcangelo, Paoletti et al, 2013). Doubtless some of these factors as well as other biological, psychological, and social factors not examined here will be identified as being associated with, and may ultimately be shown to influence, hypnotic responding.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of explicit suggestions for analgesia, hypnotizability related differences in pain thresholds (Hilgard, 1967 ; Agargün et al, 1998 ; Santarcangelo et al, 2013 ; Kramer et al, 2014 ) and perceived pain intensity (Santarcangelo et al, 2010 ) have been seldom reported. Several studies, however, describe hypnotizability-related differences in genetic polymorphisms and brain neurotransmitters content which may be relevant to pain control in the presence of suggestions and/or to the choice of pain treatments.…”
Section: Neurotransmittersmentioning
confidence: 99%
“…A correlation of the individual hypnotic susceptibility with the analgesic effect has been described for a specific analgesic suggestion with a number of investigations showing that pain reduction was more effective in high than in low hypnotizable subjects [ 8 , 15 , 16 , 32 , 33 ], even without prior induction of a hypnotic state [ 17 , 34 ]. For unspecific effects caused by general effects of hypnosis without specific suggestions the individual susceptibility does not seem to be of importance [ 15 ].…”
Section: Discussionmentioning
confidence: 99%